Emerging role of non-coding RNAs in the regulation of Sonic Hedgehog signaling pathway - Soudeh Ghafouri-Fard; Tayyebeh Khoshbakht; Bashdar Mahmud Hussen; Mohammad Taheri; Majid Samsami (Cancer Cell International, 2022)
Abstract Sonic Hedgehog (Shh) signaling cascade is one of the complex signaling pathways that control the accurately organized developmental processes in multicellular organisms. This pathway has fundamental roles in the tumor formation and induction of resistance to conventional therapies. Numerous non-coding RNAs (ncRNAs) have been found to interact with Shh pathway to induce several pathogenic processes, including malignant and non-malignant disorders. Many of the Shh-interacting ncRNAs are oncogenes whose expressions have been increased in diverse malignancies. A number of Shh-targeting miRNAs such as miR-26a, miR-1471, miR-129-5p, miR-361-3p, miR-26b-5p and miR-361-3p have been found to be down-regulated in tumor tissues. In addition to malignant conditions, Shh-interacting ncRNAs can affect tissue regeneration and development of neurodegenerative disorders. XIST, LOC101930370, lncRNA-Hh, circBCBM1, SNHG6, LINC‐PINT, TUG1 and LINC01426 are among long non-coding RNAs/circular RNAs that interact with Shh pathway. Moreover, miR-424, miR-26a, miR-1471, miR-125a, miR-210, miR-130a-5p, miR-199b, miR-155, let-7, miR-30c, miR-326, miR-26b-5p, miR-9, miR-132, miR-146a and miR-425-5p are among Shh-interacting miRNAs. The current review summarizes the interactions between ncRNAs and Shh in these contexts.